Inequality and Group Violence in Indonesia (2018) - Dona Indra Wira Budianto (Green Publisher Indonesia, 2025)
As a country with a large population, Indonesia is not free from violence. Violence in the past that often occurred was violence between state institutions and people. Meanwhile, current violence is dominated by violence between groups such as gang rivalries, street fights, fights at sports events, etc. As a developing country, Indonesia still has income inequality. This study investigates the relationships between income inequality and group violence in Indonesia. It uses The Village Potency Census (Podes) 2018 (N = 81,897) to indicate group violence, and other variables from village and district characteristics in Indonesia. The logit regression shows that inequality is significantly associated with an increase in group violence. This result says that income inequality might cause group violence because inequality triggers grievances among people which leads to group violence. Other results obtained from the logit regression are low education, poverty and unemployment which also might cause group violence. The policy implications that this study suggests are that to decrease group violence, society should be more equal and hence, income distribution, minimum educational attainment, and institutional rearrangement are important factors to consider.